Micro-arc oxidation of bioceramic coatings containing eggshell-derived hydroxyapatite on titanium substrate - Qaid, Tawfik Hamood; Ramesh, Singh; Yusof, Farazila; Basirun, Wan Jefrey; Ching, Yern Chee; Chandran, Hari; Ramesh, Subramaniam; Krishnasamy, Sivakumar (Elsevier, 2019)
In the present study eggshells-derived hydroxyapatite (EHA) coatings were successfully produced on Ti6Al4V substrates using micro-arc oxidation process (MAO) at various concentrations of EHA (i.e. 1, 1.5 and 2 g/L) in an electrolyte consisting of tri-sodium orthophosphate. The attributes of the coatings were determine by X-ray diffraction, attenuated total reflectance-fourier transform infrared spectroscopy, field emission scanning electron microscopy and energy dispersive X-ray spectroscopy. The adhesion strength was evaluated using micro scratch tester, while the corrosion behavior of the MAO-coated substrates in phosphate buffer solution was determined by an electrochemical method. The results showed that as the EHA concentration increased, this was accompanied by a reduction in the porosity due to the formation of a dense and thick coating layer. This has also resulted in an increased in the surface roughness and degree of crsytallinity of the HA phase. The MAO-coated substrate prepared with 1.5 g/L EHA concentration exhibited a well-formed coating layer with improved adhesive strength and excellent corrosion resistance. The mechanism of EHA-coating formation as well as the enhanced corrosion resistance of the coated substrates were discussed. This research shows the viability of using calcium-rich waste eggshells to produce phase pure HA suitable for coating on Ti6Al4V substrate using MAO method. © 2019 Elsevier Ltd and Techna Group S.r.l.